A Neural Dynamic Model Generates Descriptions of Object‐Oriented Actions. (5th January 2017) - Richter, Mathis; Lins, Jonas; Schöner, Gregor
Abstract: Describing actions entails that relations between objects are discovered. A pervasively neural account of this process requires that fundamental problems are solved: the neural pointer problem, the binding problem, and the problem of generating discrete processing steps from time‐continuous neural processes. We present a prototypical solution to these problems in a neural dynamic model that comprises dynamic neural fields holding representations close to sensorimotor surfaces as well as dynamic neural nodes holding discrete, language‐like representations. Making the connection between these two types of representations enables the model to describe actions as well as to perceptually ground movement phrases—all based on real visual input. We demonstrate how the dynamic neural processes autonomously generate the processing steps required to describe or ground object‐oriented actions. By solving the fundamental problems of neural pointing, binding, and emergent discrete processing, the model may be a first but critical step toward a systematic neural processing account of higher cognition.